Development Of An Automated Book Casing For Ic Industry - Chong, Kok Hen (2002)
Today, most of the IC industries are using fully automatic machines to perform the process of placing the casing onto the IC With high technology machines, daily production can be increased. However, the cost of those machines are extremely high. Therefore, the small and medium scale industries are unable to purchase these machines. In order to over come this problem, an inexpensive automatic book casing system is proposed and developed. The main objective of this project is to design a low cost machine with safety features, fully automatic and a user-friendly. This machine should be able to perform the application such punching and stamping the casing of the Integrated Circuit (IC) as well as pick and place application.The structure design of this project is separated into two parts. They are the hardware construction and the software development. The hardware part involves the design and construction of an input station, an output station, a conveyer station, a pick and place robotic arm, a punching station, a pressure faulty detection system, a power distribution module, a pneumatic control system and data logger module. The software part involves the design and development of the system control software. The system control software is created by using FPSOFT PLC programming software. FPSOFT can create the PLC programming more effectively because it uses the graphic symbol to create the PLC ladder diagram. FPSOFT is also efficient in terms of trouble shooting and programming modification. This project implements the Matsushita NAIS FPO Programmable Logic Control (PLC) to control the overall system of the machine. FPO is a simple and user friendly controller. FPO can extend its 1/O port to 128 units for large number of input and output devices control. The proposed project was successfully designed, constructed and tested. It is also working and functioning accurately as planned in its design stage. This can be shown from the experimental results conducted on the system.